How do you solve (6h-5)(6h+5)=0?

2 Answers
Apr 23, 2018

h= 5/6 or h=-5/6

Explanation:

Why do these come up in the feed if they're two years old?

(6h - 5)(6h + 5) = 0

6h-5 = 0 or 6h + 5 = 0

h= 5/6 or h=-5/6

Apr 23, 2018

h = 5/6, -5/6

Explanation:

From the null factor law, we know that if the product of two numbers is 0 then either one or both of the numbers has to equal 0. In this case your 'numbers' are 6h - 5 and 6h + 5
Therefore;
6h - 5 = 0
6h = 5
h = 5/6
and /or
6h + 5 = 0
6h = -5
h = -5/6